Does ChatGPT Have a Significant Effect to Improve EFL Preservice Teachers’ Teaching Plans? A Mixed-Method Study - Budiarta, Luh Gd Rahayu; Kusuma, I Putu Indra (Universitas Pendidikan Ganesha, 2024)
The advent of ChatGPT has surprised many English educators, as theoretically, it has many potentials to support English language teaching. However, the empirical results of how ChatGPT influence English as a foreign language (henceforth, EFL) preservice teachers’ teaching plans remain unclear. This study therefore purposed to investigate the effect of ChatGPT towards EFL preservice teachers’ teaching plans. This study employed a mixed-method approach and recruited 17 EFL preservice teachers to join the research. The data was collected using a scoring rubric and an interview protocol. Using Mann-Whitney U Test and inductive thematic analysis, this study found that the lesson plans created by EFL preservice teachers in the experimental group failed to outperform those in the control group. Moreover, the pre lesson plans had no significant difference with the post ones. The qualitative data explains the statistical results. Then, two implications were drawn to effectively use ChatGPT to support teaching and learning.